Preclinical Evaluation of a Growth‐Accommodating Transcatheter Pulmonary Valve System for Young Children - Nnaoma Agwu; Daryl Chau; Gregory S. Kelley; Tanya Burney; Ekaterina Perminov; Christopher Alcantara; Michael R. Recto; Arash Kheradvar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Congenital heart defects affect approximately 1% of births in the United States and Europe, with >1 million children in the United States living with congenital heart defects. Many experience abnormalities in the right ventricular outflow tract, often necessitating surgical intervention early in life. However, the initial repairs typically are temporary solutions as many patients will eventually need pulmonary valve replacement to address pulmonary valve regurgitation and prevent right ventricle failure. Addressing progressive pulmonary valve regurgitation, ideally in patients weighing 8 to 10 kg, is critical to prevent right ventricle dysfunction. Transcatheter pulmonary valve replacement currently treats patients weighing at least 20 kg. Unfortunately, smaller children must wait for valve replacement and risk right ventricular dilation. Methods To address this challenge, we have developed the IRIS Valve, a growth‐accommodating transcatheter pulmonary heart valve inspired by origami targeting implantation in at least 8 kg children. The valve stent underwent finite element analysis with validation by fracture testing. Using a 12‐Fr transcatheter system, the IRIS valve was implanted into 8 to 17 kg Yucatan mini pigs for 6 months. Results Benchtop fracture testing and finite element analysis confirmed the stent's ability to be crimped to a 3‐mm diameter for loading into a 12‐Fr transcatheter system and expanded to 20 mm without fracture. Animal studies successfully demonstrated excellent integration within the pulmonary valve annulus, intact valve integrity, and favorable tissue response. Conclusions The IRIS Valve offers a promising solution for earlier treatment of heart valve disease in pediatric patients with congenital heart defects, potentially improving outcomes in this vulnerable population.